Prevalence of psychotic-like experiences among Afghan migrant children and adolescents: examining the predictive role of childhood trauma, mindfulness, and cognitive flexibility - Abdul Reza Rezaee; Seyed Ruhollah Hosseini; Abbas Firoozabadi (BMC Psychiatry)
Abstract Background Psychotic-like experiences (PLEs) are subclinical phenomena that reflect mental health vulnerabilities in high-risk populations, such as migrant children and adolescents. This study aims to estimate the PLEs and their correlates in Afghan migrant children and adolescents. Methods This cross-sectional study assessed the prevalence of psychotic-like experiences (PLEs) among 770 Afghan migrant students living in Mashhad city of Iran, using the Prodromal Questionnaire-Brief Child Version (PQ-BC). The Cognitive Flexibility Inventory (CFI), Child and Adolescent Mindfulness Measure (CAMM), and Childhood Trauma Questionnaire (CTQ) were employed in univariate and multivariate models to examine psychological and trauma-related correlates of PLEs. Results The findings showed that 94% of participants reported experiencing at least one psychotic-like experience. Additionally, 34% of Afghan migrant children and adolescents met the cutoff point, and experienced significant distress. Psychotic-like symptoms were more prevalent in adolescents than in children (OR = 1.946). Emotional abuse (OR = 1.123), a subscale of childhood trauma, along with mindfulness (OR = 0.925) and cognitive flexibility (OR = 1.038), were identified as correlates of psychotic-like experiences. In aggregate, all correlates of PLEs explained 22% of the variance in the outcome variable for children and 29% for adolescents. These results contribute to a deeper understanding of the factors influencing psychotic-like experiences within migrant populations. Conclusion These results show that PLEs are common among Afghan migrant children and adolescents, a marginalized minority group. While some theories might explain these findings, the results highlight the need for mental health services to pay closer attention to this population.